Synthesis and characterization of o-fluorosulfinylaniline: A comparative vibrational study of fluorinated sulfinylaniline series - Paez Jerez, Ana Laura (2015)
The synthesis of o-fluorosulfinylaniline is reported with the aim to complete the fluorinated sulfinylaniline series. The FT-IR and Raman spectra of o-fluorosulfinylaniline are recorded and the fundamental modes of its vibrational frequencies are assigned together with a tentative assignment of the NMR and mass spectra. Quantum chemical calculations on the optimized geometry predict in the liquid phase a planar structure with syn orientation of the –N[double bond, length as m-dash]S[double bond, length as m-dash]O moiety (syn of the S[double bond, length as m-dash]O double bond relative to the C–N single bond), which belongs to the CS symmetry group. The experimentally observed spectral data (FT-IR, Raman, 1H and 13C and GC-mass spectrometry) of the title compound are compared with those obtained theoretically from DFT calculations and the gauge including atomic orbital (GIAO) method. Vibrational frequencies were assigned with the aid of anharmonic variational methods (VSCF) obtaining a significantly better agreement with experiment than with simple harmonic oscillator methods. Moreover, stability of the molecule arising from hyperconjugative interactions and charge delocalization has been analyzed using natural bond orbital (NBO) analysis.